2017
DOI: 10.1063/1.4998311
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction p-Cu2O/n-Ga2O3 diode with high breakdown voltage

Abstract: Heterojunction p-Cu2O/n-β-Ga2O3 diodes were fabricated on an epitaxially grown β-Ga2O3(001) layer. The reverse breakdown voltage of these p-n diodes reached 1.49 kV with a specific on-resistance of 8.2 mΩ cm2. The leakage current of the p-n diodes was lower than that of the Schottky barrier diode due to the higher barrier height against the electron. The ideality factor of the p-n diode was 1.31. It indicated that some portion of the recombination current at the interface contributed to the forward current, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(88 citation statements)
references
References 30 publications
0
79
0
Order By: Relevance
“…The layer thicknesses used in this study are not sufficient to determine a breakdown field. However, the reverse voltages discussed here are much lower than breakdown voltages mentioned in the literature for pn‐heterodiodes or Schottky barrier diodes . In order to achieve such high breakdown voltages, thicker Ga 2 O 3 layers or a lower doping could be used.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The layer thicknesses used in this study are not sufficient to determine a breakdown field. However, the reverse voltages discussed here are much lower than breakdown voltages mentioned in the literature for pn‐heterodiodes or Schottky barrier diodes . In order to achieve such high breakdown voltages, thicker Ga 2 O 3 layers or a lower doping could be used.…”
Section: Resultsmentioning
confidence: 82%
“…The Cu 2 O/Ga 2 O 3 heterodiodes were fabricated on commercially available epitaxial n‐Ga 2 O 3 on Ga 2 O 3 substrates. A direct comparison of Cu 2 O/Ga 2 O 3 heterodiodes with platinum Schottky diodes on one and the same thin film was reported . The pn‐heterodiodes and the platinum Schottky diodes exhibit breakdown voltages of 1.49 and 0.67 kV, respectively.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ga 2 O 3 SBD starts to present its potential in power electronics applications.
Fig. 4The development of Ga 2 O 3 SBD in recent years [16, 18, 62, 6871]
…”
Section: Schottky Barrier Diode Based On β-Ga2o3mentioning
confidence: 99%
“…In 2017, T. Watahiki et al from Mitsubishi Electric Corporation reported a heterojunction p-Cu 2 O/n-Ga 2 O 3 p-n diode without local termination structure [71]. Figure 11 shows the schematic, band diagram and J–V curves of this p-n diode.…”
Section: Schottky Barrier Diode Based On β-Ga2o3mentioning
confidence: 99%